Hubungan Latar Belakang Pendidikan terhadap Aktivitas Fisik Generasi Alpha Usia 13-15 Tahun - Ibagas Riskyanto Pamungkas; Intan Lailatul Nikmas; Mohammad Noval Baghaskara (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
The increasing integration of digital technology into the daily lives of Generation Alpha has contributed to reduced physical activity, highlighting the need to understand the factors shaping children’s movement behaviors. This study employed a quantitative correlational approach to examine the relationship between parental educational background and the physical activity levels of students aged 13–15 at SMP 1 Waru Sidoarjo. Data were collected through a parental education questionnaire and the PAQ-C instrument, which assesses children’s physical activity over the past seven days. A total of 45 respondents participated, and the data were analyzed using Pearson or Spearman correlation tests, depending on distribution. The findings revealed a positive and statistically significant—though weak—association between parental education and children’s physical activity levels. Parents with higher education tend to promote more active lifestyles by regulating screen time, providing access to sports facilities, and modeling healthy behaviors. These results underscore the essential role of families in developing healthy routines among Generation Alpha and the need for educational initiatives to enhance parental awareness of physical activity in an increasingly digital environment.